Personality and dream content: are dreams, dreamer’s footprints? - Khalil, Rehana (International Journal Of Community Medicine And Public Health, 2017)
Background: A series of thoughts, images, and sensations occurring in a person’s mind during sleep is known as a dream. Relationship of dreams and dreamer has been studied in different perspectives quite extensively. The present study is focused on dream content and personality type. Methods:A sample of 370 randomly selected participants by nonprobability convenience sampling from Karachi, Pakistan. Questionnaire with close ended and open ended questions had two sections: 1) Personality analysis; 2) Dream analysis. Eysenck personality questionnaire (EPQ) which is the most widely used psychological instrument for measuring the extraversion-introversion with 5-point Likert scale was utilized. The data from the questionnaire was cleaned, coded and entered in Excel (Microsoft, Redmond, WA, USA), exported to SPSS version 21 for windows (SPSS Inc, Chicago, Illinois, USA), for analysis. Descriptive and inferential statistics were used to analyse the data. Results: Among the 370 subjects, 54% were males and 46% were females. Median age of the study sample was 16 years. The educational level of half (50%) of the sample was masters. The data was organized in nine themes included trepidation, daze, contentment, dejection, flashbacks/past life events, symbolic, problem solving/precognition dreams, reflective dreams, and creative dreams. The frequency of almost all types of dreams was high among extroverts as compared to introverts except introverts reported a statistically high frequency of past events in their dreams. One distinguishing dream found exclusively among extroverts was about being somebody else e.g., an actor. Feeling of climbing or jump from a height was only perceived by the extroverts, surprisingly not at all by any of the introvert. The frequency of creative dreams (an innovative idea) and dreams of fight or quarrel, writing some type of information in open spaces, flight and falling were found to be same in both types of dreamers. Conclusions:Even-though the difference in all dream content of extroverts and introverts was not significant but my study does not support the idea of no impact of personality on dreaming. The present study was an attempt to demonstrate relationship between difference in dream content and personality type. Future studies are needed to do an advance research in this dimension of dreaming.